Are students kidding with health research ethics? The case of HIV/AIDS research in Cameroon - Munung, Nchangwi Syntia (BioMed Central, 2012)
BACKGROUND: Universities in Cameroon are playing an active part in HIV/AIDS research and much of this research is carried out by students, usually for the purpose of a dissertation/thesis. Student theses/dissertations present research findings in a much more comprehensive manner and have been described as the stepping-stone of a budding scientist’s potential in becoming an independent researcher. It is therefore important to verify how students handle issues of research ethics. METHOD: Theses/dissertations on HIV/AIDS that described research studies involving the use of human research participants were screened to verify if research ethics approval and informed consent were obtained and documented. The contents of the consent forms were also qualitatively analyzed. RESULTS: Of 174 theses/dissertations on HIV, ethics approval was documented in 17 (9.77%) and informed consent in 77 (47.83%). Research ethics approval was first mentioned at all in 2002 and highly reported in the year 2007. Evidence of ethics approval was found for the first time in 2005 and informed consent first observed and evidenced in 1997. Ethics approval was mostly reported by students studying for an MD (14.01%) and was not reported in any Bachelors’ degree dissertation. Informed consent was also highly reported in MD theses (64.58%) followed by undergraduate theses (31.58%). Voluntary participation and potential benefits of the study were some of the common aspects dealt with in most of the consent forms. The right to discontinue participation in the study and management of residual samples were scarcely ever mentioned. CONCLUSIONS: Overall, and given the current state of the art of research ethics around the world, student-scientists in Cameroon would seem to be merely kidding with research ethics. It is thus essential that training in health research ethics (HRE) be incorporated in the curriculum of universities in Cameroon in order that the next generation of scientists may be better equipped with thorough knowledge and practice of HRE. This, we believe, would be one way of fighting the occurrence of research scandals, which have not yet abated significantly, especially those arising from negligence or inexcusable ignorance.